Analisis Penerapan Good Corporate Governance Pada Kantor Kecamatan Sumobito - Pravitasari, Tanty Putri; Febryani, Irma Ika; Djasuli, Mohamad (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2022)
The purpose of this study is to understand the forms and practices of good governance in the Sumobito District office. This study uses a qualitative descriptive analysis technique. This study found that the implementation of Good Corporate Governance in the Sumobito District Office was in accordance with the mechanism of good governance although there were still some weaknesses in its implementation in the field.